Cara Tanam dan Pemupukan Tanaman Kacang Hijau di Lahan Kering Iklim Kering Sumba Timur, Nusa Tenggara Timur - Sri Ayu Dwi Lestari; Sutrisno Sutrisno; Henny Kuntyastuti (Institut Pertanian Bogor, 2021)
The intercropping method is one way to maximize plants and soil's utilization in a dry land. This study aimed to determine the cultivation (cropping methods and fertilization) that could increase mungbean grain yield in dry land in the dry climate of East Sumba, East Nusa Tenggara Province. The experiment was conducted at dry land in a dry climate in Laipori Village, Pandawai District, East Sumba Regency in 2017. The experiment was laid out in a split-plot design with four replications. The main plot was a cropping pattern, namely (1) intercropping mungbean with maize. Mungbean plant spacing was 30 cm ´ 20 cm, two plants per hole, and maize plant spacing was (50 cm ´ 50 cm) ´ 120 cm, one plant/hole and (2) mungbean monoculture with a plant spacing of 40 cm ´ 10 cm, two plants/hole. The subplot was dosage and type of fertilizer, namely (1) 150 kg Phonska/ha, (2) 5000 kg cow manure/ha, and (3) 75 kg Phonska + 2500 kg cow manure/ha. The mungbean variety used was Vima 1, and the maize variety was Bima. The results showed that intercropping mungbean with maize could increase the yield of mungbean seeds yield by 0,28 t/ha (51,85%) and increase the mungbean biomass by 0,31 t/ha (22,30%) compared to the monoculture system. Different types and dosages of Phonska inorganic fertilizer and cow manure did not cause differences in the mungbean yield.